(PhC(NtBu)2Al)2(SiH2)4 six-membered heterocycle: comparable in structure to cyclohexane. Issue 16 (6th February 2019) - Li, Jiancheng; Zhong, Mingdong; Keil, Helena; Zhu, Hongping; Herbst-Irmer, Regine; Stalke, Dietmar; De, Sriman; Koley, Debasis; Roesky, Herbert W.
Abstract : A (PhC(N t Bu)2 Al)2 (SiH2 )4 centrosymmetric six-membered heterocycle (LAl)2 (SiH2 )4 (L = PhC(N t Bu)2 ) with chair conformation is prepared by reacting disilylene LSi–SiL with alane AlH3 ·NEtMe2 . It is comparable in structure to cyclohexane containing four Si and two Al atoms as a core. Abstract : A silicon–aluminum heterocycle LAl(SiH2 SiH2 )2 AlL (L = PhC(N t Bu)2 ) (1 ) was prepared. Compound1 exhibits a unique (N2 Al)2 (SiH2 )4 centrosymmetric six-membered ring structure with a chair conformation, which is comparable with that of cyclohexane. Furthermore, two intermediate analogues, silylene–alane adduct LSi(AlMe3 )–Si(AlMe3 )L (2 ) and silylene–alane oxidative product [LAlHSiH2 Mes]2 (3 ) were obtained. Compound3 has an interesting arrangement of an Al–H and an SiH2 unit, which are in close vicinity to each other.3 might be important to function as a catalyst, due to the already activated bridging Al–H bonds.